2019
DOI: 10.1021/acscatal.9b04110
|View full text |Cite
|
Sign up to set email alerts
|

Intermediacy of Copper(I) under Oxidative Conditions in the Aerobic Copper-Catalyzed Decarboxylative Thiolation of Benzoic Acids

Abstract: An experimental mechanistic study of the aerobic copper-catalyzed decarboxylative thiolation of benzoic acids with aryl thiols is reported. For the model reaction, the findings support the corresponding disulfide (PhSSPh) of the aryl thiol (PhSH) as the active thiolating source under reaction conditions. Synthesis and reactivity studies along with kinetic measurements support the chemical and kinetic competence of catalytically active welldefined Cu-complexes; (phen)Cu I (O2CC6H4-o-NO2) (2), (phen)Cu I (C6H4-o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…They also demonstrated that diphenyl diselenide could be an efficient coupling partner, leading to the desired diaryl selenide in 53% yield. Based on mechanistic studies, a pathway was proposed [300] which commences with the decarboxylation of a (Phen)Cu(I)‐carboxylate to form an aryl‐Cu(I) species (Scheme 46B). This intermediate undergoes oxidative addition of the ArSSAr thiolating reagent generated via Cu‐mediated aerobic oxidation of the initial ArSH.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 99%
“…They also demonstrated that diphenyl diselenide could be an efficient coupling partner, leading to the desired diaryl selenide in 53% yield. Based on mechanistic studies, a pathway was proposed [300] which commences with the decarboxylation of a (Phen)Cu(I)‐carboxylate to form an aryl‐Cu(I) species (Scheme 46B). This intermediate undergoes oxidative addition of the ArSSAr thiolating reagent generated via Cu‐mediated aerobic oxidation of the initial ArSH.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 99%
“…The mechanisms of metal-catalyzed protodecarboxylation and decarboxylative cross-coupling reactions have been studied. ,, In contrast to systems that use Ag , or Cu , additives, systems utilizing only a Pd catalyst are much less well understood. Unlike decarboxylative Heck reactions or protodecarboxylation reactions, there is minimal experimental mechanistic data on palladium-catalyzed decarboxylative cross-coupling without copper or silver. A variety of palladium-catalyzed methods have been developed including work by Bilodeau and Forgione on coupling heteroarylcarboxylic acids, , a report by Eli Lilly to synthesize a desired scaffold, , and advancement of intramolecular cyclizations by Shen, , in addition to others. , However, these reactions have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanistic follow-up study suggested that the catalytic cycle proceeds via decarboxylation of the Cu(I) carboxylate complex A to a Cu(I) aryl species B, which undergoes oxidative addition with the in situ formed disulfide. 103 Similar reaction conditions were applied to convert benzylic alcohols to thioethers via oxidative cleavage of the CAr-C(OH) bond and subsequent decarboxylation. 104 Other reported achievements include couplings of alkynyl carboxylic acids, 105 methylthiolations using DMSO, 106 and syntheses of perfluoroalkyl thioethers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%